ANALISIS PENGARUH LOGISTIK, TARIF MASUK BARANG, NILAI INDUSTRI TERHADAP NILAI EKSPOR BARANG NEGARA-NEGARA ASIA TIMUR PASIFIK - Muhammad Glenn Yunifer; Marselina Marselina (Universitas Islam Lamongan, 2022)
The purpose of this study was to analyze the effect of logistics performance, import tariffs and industrial value added on the value of exports of goods in East Asia Pacific countries for the 2010-2020 period, either partially or simultaneously. The analytical techniques used are model suitability testing, classical assumption testing, multiple linear regression analysis, hypothesis testing with t test and F test and testing the coefficient of determination. The results showed that logistics performance had a positive and significant effect on the value of exports of goods, import tariffs on goods had a negative and significant effect on the value of exports of goods, industrial value added had a positive and significant effect on the value of exports of goods. Logistics performance, goods entry rates,